An Insight Into the Practical Training of Fine Art Student Teachers in Slovenia Through Their Visual and Multimodal Reflections - Marinšek, Miha; Hmelak , Maja (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
An important aspect of the teaching practice of future art educators is the development of their reflection skills. Writing reflections can be of great help to students in this regard. In the academic year 2021/22, students reflected on guided practice in the form of a visual essay. We were interested in how students experience practical training. We were particularly interested in the kind of messages students offer about practical training when they can express themselves visually. We used a visual research approach, as visual research strategies are a direct and tangible way of understanding the experience of the participants. We found that the visual essays differed in their artistic expression and the content that students wanted to emphasize (awareness of one's own body, experiencing progress, experiencing effort and uncertainty, the contrast between fears before the performance and pleasant feelings after the performance, time constraints, etc.).